«Bleuet» by the Guillaum Apolliner`S poem: the first war song by Francis Poulenc - Rizaieva, Ganna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
Relevance of the study. The vocal miniature Bleuet is one of the pearls of Poulenc's chamber and vocal work. This is evidenced by its numerous performances at concerts dedicated to the remembrance of those killed in the First World War. However, even on the pages of the fundamental monographs of the leading European researchers of Poulenc's work, this opus is given literally a few lines, and it’s absolutely absent in the Ukrainian musicological space. The lack of research on the vocal miniature Bleuet, its indisputable importance for a deeper understanding of the whole artistic world of Francis Poulenc, as well as the exceptional topicality of the subject of this mélodie in the modern Ukrainian context determine the relevance of its research. The main objective of the study is to reveal the specificity of Francis Poulenc's creative awareness of the war’s subject through Guillaume Apollinaire's poetry in mélodie Bleuet ("Cornflower"). The scientific novelty is determined by the fact that Francis Poulenc's chamber-vocal miniature Bleuet by the Guillaume Apollinaire’s words is being investigated in Ukrainian musicology for the first time. The methodology of the article is based on historical, biographical, phenomenological and genre-stylistic research methods of analysis. Results / findings and conclusions. Bleuet (1939) is one of the most inspired mélodies in the work by Francis Poulenc. A moving epitaph to a young recruit, imbued with a sense of humility and tenderness, it’s the first creative realization by the compositor of the Second World War’s tragedy. This miniature appears in the same row as the great compositor's monumental works, which reflect his spiritual search and are an echo of the deep religious consciousness. Patriotism is interpreted through the sacredness of the sacrifice of a young man who "knows death better than life." The lyricism that permeates the mélodie is extremely intimate in its essence. To some extent, the autobiographical nature of the recruit's image (due to the events of the First World War in the life of the composer) is significantly strengthened by the commonality of the situation's archetype with Blanche de la Force (the main character of the opera Dialogues of the Carmelites), with whom Francis Poulenc personified himself while working on the opera. This proves that Poulenc never sought to separate his creativity from his own “I”. Regardless of the specifics of the chamber genre mélodie and the brevity of Bleuet (54 measures), due to the multi-layered and meaningful poetry by Guillaume Apollinaire, Francis Poulenc's miniature impresses with its depth, semantic polyphony, a kind of "crucifixion" between the verbal series and the musical text.